The Community and its Political Challenges in a Radical Democracy - José Antonio Figueroa (Íconos)
From the creation and dissolution of two peasant communities in Nono, a rural parish of Quito, this article reflects on the political and economic role assigned to peasant and indigenous communities in the Ecuadorian Constitution of 2008 and in the Law of the Popular and Solidarity Economy. In the article, the notion of community is read critically as it maintains that communities are not essential attributes of peasants, indigenous peoples, or popular sectors, but rather the result of possible political arrangements and negotiations put forth by those who comprise communities. Debates over community are covered and the academic and political values community can have in Ecuador today are analyzed.